Computer Vision and Graphics [electronic resource] : International Conference, ICCVG 2014, Warsaw, Poland, September 15-17, 2014. Proceedings - Chmielewski, Leszek J.; Kozera, Ryszard; Shin, Bok-Suk.; Wojciechowski, Konrad; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the International Conference on Computer Vision and Graphics, ICCVG 2014, held in Warsaw, Poland, in September 2014. The 81 full papers presented were carefully reviewed and selected from various submissions. They cover various important aspects of computer vision and graphics.
Combined metrics for color image quality assessment -- Quartic orders and sharpness -- Parallel simulation -- Mandelbrot- and Julia-like rendering -- Time compensation in perceptual experiments -- Fur visualization for computer game engines -- Multiple scattering in cumulus clouds -- Component weight tuning of SSIM image quality assessment measure.
Keywords: Computer science; Algorithms; Computer graphics